Visible-infrared dual-mode MoS2-graphene-MoS2 phototransistor with high ratio of the Iph/Idark. (14th September 2018) - Deng, Wenjie; Chen, Yongfeng; You, Congya; An, Boxing; Liu, Beiyun; Li, Songyu; Zhang, Yongzhe; Yan, Hui; Sun, Ling
Abstract: 2D materials such as graphene and transition metal dichalcogenides exhibit novel electrical and optoelectrical properties, which are promising for the application in sensing and imaging. However, the photoresponse ability of pure monolayer graphene in room temperature and ratio of I ph and I dark are still unsatisfactory, due to the weak light absorption itself, short lifetime of photo-excited carriers and large dark current, especially in the infrared range. Here, we successfully constructed a broadband graphene-based phototransistor consisting of lateral MoS2 -graphene-MoS2 heterostructure by chemical vapor deposition technique. It shows broadband photodetection and a low dark current less than 1 pA at applied bias of 0.5 V, resulting in excellent specific detectivity more than 10 12 Jones and nearly 10 9 Jones in visible and infrared band, respectively. Moreover, the ratio of I ph and I dark could be modulated by the back-gate voltage when the phototransistor is under the infrared illumination. And a high ratio of 10 5 was exhibited. This type of graphene-based phototransistor by chemical vapor deposition demonstrates an approach for the room temperature broadband photodetection of monolayer graphene by energy engineering. All the results address key challenges for broadband detection by graphene-based phototransistor, and are promising for the large scale fabrication and integration in the future electronic and optoelectronic applications.